Students' Sexual Violence Understanding: Educating XI Grade Students of SMK Muhammadiyah Bojong through the Film “Penyalin Cahaya” - Salsabila, Salma; Fajar, Dwi Ario (Universitas Muhammadiyah Semarang, 2024)
This study examines sexual violence understanding among 11th-grade students at SMK Muhammadiyah Bojong, influenced by the film